2017
DOI: 10.3846/1648715x.2017.1409290
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Beam Plus Certification on Property Price in Hong Kong

Abstract: In response to the public’s increasing awareness of sustainable development, the construction industry has introduced “green” buildings which emphasize better environmental performance. However, as a building’s environmental performance is difficult to discern for laymen, different green building certifications have been established for evaluations in this regard. This study evaluates whether there exists a price premium for living space in buildings certified with BEAM Plus. The findings show that the prices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…In Hong Kong, Building Environmental Assessment Method (BEAM) Plus is one of the green-building certifications. Compatible with internationally-renowned green-building certifications such as LEED and BREEAM, the original intent of BEAM Plus was to be a voluntary scheme for the assessment of buildings' environmental performance [35]. The International Initiative for a Sustainable Built Environment (iiSBE) developed the SBTool assessment method to rate the sustainability performance of buildings, which focuses on the environmental, economic as well as social aspects of sustainability [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Hong Kong, Building Environmental Assessment Method (BEAM) Plus is one of the green-building certifications. Compatible with internationally-renowned green-building certifications such as LEED and BREEAM, the original intent of BEAM Plus was to be a voluntary scheme for the assessment of buildings' environmental performance [35]. The International Initiative for a Sustainable Built Environment (iiSBE) developed the SBTool assessment method to rate the sustainability performance of buildings, which focuses on the environmental, economic as well as social aspects of sustainability [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To examine the financial implications of BEAM, BEAM Plus and LEED certifications on the value of rental office space in Hong Kong, the study deployed a hedonic price model through a fixed effects approach. Despite some weaknesses (assumptions), the hedonic model (HPM) is regarded as an effective tool in the area of property valuation analysis (Hui et al, 2015;Hui, Tse, & Yu, 2017). For example, using HPM, the effects of structural attributes such as floor area, age and size of the unit, etc.…”
Section: The Modelmentioning
confidence: 99%
“…As another positive impact on the appearance of the resultant of EPC is a price premium. By investigating the impact of EPC on house price, some studies have found that the price premium is positively related to a higher EPC level [16,17]. Fuerst et al (2016) [16] conclude that in the UK there are positive price premiums for houses in higher efficiency rates (A/B and C), and there are discounts for lower efficiency rates (E and F).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fuerst et al (2016) [16] conclude that in the UK there are positive price premiums for houses in higher efficiency rates (A/B and C), and there are discounts for lower efficiency rates (E and F). Hui et al (2017) [17] shows that prices of energy certified buildings are 4.4 percent higher than those of non-registered buildings in Hong Kong.…”
Section: Literature Reviewmentioning
confidence: 99%